2016
DOI: 10.2174/1381612822666160303110838
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in Hepatocellular Carcinoma: Potential Diagnostic and Prognostic Biomarkers

Abstract: Hepatocellular carcinoma (HCC) is one of the most common types of malignancies worldwide. There is little information on the mechanisms involved in the pathogenesis of this disease. Diagnosis of HCC at early stages would be crucial for increasing the survival of patients. Circulating miRNAs have emerged as one of the most attractive tools for an early diagnosis of cancers. Various studies have shown that there is an aberrant expression of miRNAs such as miR-25, miR-375, miR-206, miR-223, miR- 92a, miR-222, miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 147 publications
1
109
0
Order By: Relevance
“…MiRNAs are known as small non‐coding RNAs which have central roles in vital physiological events such as apoptosis, angiogenesis, growth, and differentiation (Gholamin et al, ; Goradel et al, ; Hashemi Goradel et al, ; Reza Mirzaei et al, ; Salarinia et al, ). Hence, deregulation of these molecules could lead to activation/inhibition various molecular and cellular targets which could contribute to initiation and progression of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs are known as small non‐coding RNAs which have central roles in vital physiological events such as apoptosis, angiogenesis, growth, and differentiation (Gholamin et al, ; Goradel et al, ; Hashemi Goradel et al, ; Reza Mirzaei et al, ; Salarinia et al, ). Hence, deregulation of these molecules could lead to activation/inhibition various molecular and cellular targets which could contribute to initiation and progression of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Many miRNAs may be relevant as diagnostic and prognostic biomarkers for HCC patients [25,26]. We herein provide data for clinical samples obtained from 130 HCC patients, which revealed that high miR-650 levels and low LATS2 levels are associated with unfavorable clinical features and poor outcomes.…”
Section: Discussionmentioning
confidence: 92%
“…miRNA-21 or miR-21is an oncogenic miRNA and it is overexpressed in many human cancers including HCC, particularly plasma miR-21 proved to a novel circulating biomarker for HCC (Kamel et al, 2016; Mirzaei et al, 2016). Tomimaru et al reported circulating miR-21 as a novel biomarker for HCC where HCC patients' plasma were measured for miR-21 by qRT-PCR after pre and post-surgical resection.…”
Section: Current Treatment Modalities For Hepatocellular Carcinomamentioning
confidence: 99%